Terpenoid profiles of the essential oils from the underground parts of Dianthus thunbergii S.S. Hooper and Hypoxis argentea Harv ex Baker as affected by pre-distillation drying (2024)
The roots of Dianthus thunbergii and corms of Hypoxis argentea are commonly used in the Eastern Cape Province of South Africa for various medicinal purposes, although their effectiveness as fresh or dried forms is often a subject of debate. The compositions of the volatile oils from the underground parts of these plants were analyzed for the first time by gas chromatography-mass spectrometry (GC-MS). The yields of the essential oil fractions from fresh and oven-dried plant parts varied from 0.42-0.72%. The terpenoid composition of D. thunbergii oils were dominated by α-pinene and β-selinene, although overall terpenoid content decreased from 77.17% in fresh roots to 47.58% in the dried roots. H. argentea corm oils were dominated by alkanes, amides and amino acids, while total terpenoid content of the oils from fresh and dried corms were 10.85% and 3.45%, respectively. Generally, pre-distillation drying of the underground parts of both plants produced significant reductions in the terpenoid composition of the volatile oils, suggesting that drying may considerably reduce their medicinal potentials.